High frictional stability of braking material reinforced by Basalt fibers. (February 2023) - Yu, Kun; Shang, Xi; Zhao, Xiaoguang; Fu, Liangjie; Zuo, Xiaochao; Yang, Huaming
Abstract: Frictional stability is a more accurate description of the friction state than coefficient of friction (COF) and wear rate. This work aims to develop Basalt fiber (BF)-reinforced braking material as high frictional stability friction materials. The findings demonstrate that using the BF can improve the mechanical, thermal properties and COF of the brake material while also enhancing the frictional stability, and restricting the friction fluctuation range between 0.040 and 0.110. The mechanism of frictional stability of BF is explained in detail under macro and micro levels. This work is expected to provide some reference value for the design and development of fiber-reinforced friction composites and the mechanism for interpretation of friction stability. Highlights: Non-asbestos organic (NAO) brake pads with high frictional stability were fabricated. The braking materials with basalt fiber (BF) exhibit extremely low friction fluctuation. The mechanism of frictional stability of BF is explained in detail under macro and micro levels. The ANN model has a strong capacity to predict the COF and frictional stability after training.